(untitled) (KYAMC Journal, 2013)
Background: All women go through menopause stage after a certain age and menopause women suffer from different medical problems which needs specific attention. Aim: The aim of the study is to find out the consequences of postmenopausal women attending in the hospital for medical treatment. This study also identifies the outcome of different consequences in those patients. Methods: Among 105 patients were selected for the study purposively those who were admitted in the gynecological ward in Kumodini Women’s medical college from March 2008 to February 2009. All patients were undertake clinical examination and find out the consequence of menopause in one year observation period. A structured questionnaire was used to interview the patient and information also collected from patient’s treatment file. Statistical analysis was performed by using statistical software SPSS 11.5 window. Results: Among 105 patients, age was above 40 years. Most of the patients were coming from low and low middle income society having maltiparous We have examined that most of the menopausal women developed uterovaginal prolapse was 63.8%, genital malignancies was found among 17.4% patients and rest were faced other benign disorders (19%) which includes leiomyoma, pelvic inflammatory diseases (PID), uncontrolled bleeding, urinary tract infections (UTI) and ovarian cysts. Conclusions: In Post menopausal phase of women in Bangladesh suffered from different health consequences like uterine prolapse, benign diseases and carcinoma which causes of hospital admission for better management. KYAMC Journal Vol. 3, No.-2, January 2013, Page 290-293 DOI: http://dx.doi.org/10.3329/kyamcj.v3i2.15169